Leading from the Library : Help Your School Community Thrive in the Digital Age - Miller, Shannon (Shannon McClintock); Bass, William L., 1973- (Book collections on Project MUSE., 2019)
"In this book, a librarian and an education leader team up to reflect on the librarian?s ability to build connections in two ways. First, they discuss the benefits of bringing the outside world into the library through the use of social media, videoconferencing and other tools that allow librarians to partner with others. Then they expand upon these connections by addressing how librarians can lead in the greater educational community by sharing resources and strategies, and partnering with school leaders to tell the story of the school community." "Through this book, librarians will discover the influence they can have on the school community as the library becomes the heart of the school, a place where problems are solved, content is explored, connections are made and discovery happens." --Back cover.